2012
DOI: 10.1111/j.1469-8137.2012.04175.x
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐mount confocal imaging of nuclei in giant feeding cells induced by root‐knot nematodes in Arabidopsis

Abstract: Summary• Excellent visualization of nuclei was obtained here using a whole-mount procedure adapted to provide high-resolution images of large, irregularly shaped nuclei. The procedure is based on tissue clearing, and fluorescent staining of nuclear DNA with the dye propidium iodide.• The method developed for standard confocal imaging was applied to large multicellular root swellings, named galls, induced in plant hosts by the root-knot nematode Meloidogyne incognita.• Here, we performed a functional analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 45 publications
4
42
1
3
Order By: Relevance
“…The mechanisms used to regulate the deposition of new material to the CW and its thickening vary, and as the giant cells form, highly reticulated regions are created from these expansion zones that resemble CW labyrinths called "invaginations", through which the transportation of solutes into and out of the giant cell intensifies (Vieira et al, 2012;Rodiuc et al, 2014). Such invaginations develop throughout the process of maturation of the nematode and degenerate once it reaches its maturity and completes its life cycle (Rodiuc et al, 2014).…”
Section: Modifications Of the Cw During The Formation Of The Sfs Indumentioning
confidence: 99%
“…The mechanisms used to regulate the deposition of new material to the CW and its thickening vary, and as the giant cells form, highly reticulated regions are created from these expansion zones that resemble CW labyrinths called "invaginations", through which the transportation of solutes into and out of the giant cell intensifies (Vieira et al, 2012;Rodiuc et al, 2014). Such invaginations develop throughout the process of maturation of the nematode and degenerate once it reaches its maturity and completes its life cycle (Rodiuc et al, 2014).…”
Section: Modifications Of the Cw During The Formation Of The Sfs Indumentioning
confidence: 99%
“…11,15 Recently, we initiated a detailed functional analyses of the Arabidopsis KRP gene family during RKN [Meloidogyne incognita (Kofoid and White, 1919) Chitwood, 1949] infection, in order to reveal their potential involvement on this plant-pathogen interaction. 16,17 Of the 7 Arabidopsis genes, we observed that 3 members of this family (KRP2, KRP5, and KRP6 ) were highly expressed during at least a certain time span of nematode feeding root-knot nematodes (rKn) are highly specialized, obligatory plant parasites. these animals reprogram root cells to form large, multinucleate, and metabolically active feeding cells (giant cells) that provide a continuous nutrient supply during 3-6 weeks of the nematode's life.…”
Section: How Do Root-knot Nematodes Alter the Host Genetic Program?mentioning
confidence: 99%
“…25,26 KRP1 and KRP4 proteins present both nuclear and sub-nuclear localization and co-localize with chromosomes during mitosis. 16,26 KRP2 is evenly distributed in the interphase nucleus and apparently degraded during mitosis. 17 The different sub-nuclear protein localization of KRPs (like KRP1, KRP3, KRP4, and KRP5), suggests diverse roles of these proteins in plant cells.…”
Section: Enhanced Host Krp Levels Disrupt Cell Cycle Progression In Gmentioning
confidence: 99%
See 2 more Smart Citations